Influence of Plant Growth-Promoting Rhizobacteria (PGPR) Inoculation on Phenolic Content and Key Biosynthesis-Related Processes in Ocimum basilicum Under Spodoptera frugiperda Herbivory - Jimena Sofía Palermo; Tamara Belén Palermo; Lorena del Rosario Cappellari; Gerd Ulrich Balcke; Alain Tissier; Walter Giordano; Erika Banchio (Plants)
Plants are naturally subjected to various types of biotic stresses, including pathogenic microorganisms and herbivory by insects, which trigger different signaling pathways and related defense mechanisms. Inoculation with microorganisms, such as plant growth-promoting rhizobacteria (PGPR), can be seen as a form of stress because it triggers a systemic resistance response in plants similar to that caused by insect herbivory. However, these interactions have typically been studied independently, which has limited the understanding of their combined effects. This study examines the effects of Bacillus amyloliquefaciens GB03 inoculation and Spodoptera frugiperda herbivory on the total phenolic contents of Ocimum basilicum. We also analyze the levels of endogenous phytohormones and the activity of phenylalanine ammonia-lyase (PAL), a crucial enzyme involved in the biosynthesis of phenolic defense-related metabolites. The results indicate that the total phenolic content significantly increased only in plants that were both inoculated by GB03 and damaged by larvae. Additionally, PAL activity showed an increase in plants that were damaged by larvae and in those subjected to the combined treatment of larval damage and inoculation with GB03. Regarding phytohormones, in plants damaged by insects, the levels of salicylic acid (SA) increased, regardless of whether they were inoculated or not, while the levels of jasmonic acid–isoleucine (JA-ile) rose in all treatments compared to the control. This study highlights the intricate relationships among beneficial microbes, herbivores, and plant defense mechanisms, emphasizing their potential impact on improving plant resilience and the production of secondary metabolites. Furthermore, understanding the independent effects of PGPR inoculation, beyond its interaction with herbivory, could provide valuable insights into its role as a sustainable alternative for enhancing plant defense responses and promoting crop productivity.